Minimize Defects in 5 Liters Jerry Cans by Using Statistical Quality Control and Root Cause Analysis - Bayu Bisma Nanda; Wiwik Sulistiyowati (PROZIMA (Productivity, Optimization and Manufacturing System Engineering), 2020)
PT. DS2 is one of the producers of household appliances, kitchen utensils, and children's toys to bottles and jerry cans, to produce 5 liters of jerry using 2 Blow Molding machines that can produce an average jerry of 6750 / plastic jerry per day. In the production process there are defects found in 5 liter jerry products. This study aims to determine the cause of defect, what factors cause defect. Method used in this research is SQC and RCA in an effort to determine the defect in the 5 liter jerry production process. From the results of research that has been done, the highest value of disability is PL bloom defect with 1686 pcs with a cumulative percentage of 41%. Based on the analysis using the control p chart that all percentages of defective pruduct are still in the control chart and declared safe.